PROTOTYPE PENGOLAHAN LIMBAH BATANG DAN TANDAN KOSONG KELAPA SAWIT SEBAGAI BAHAN BAKU PULP - Hasmawaty AR; Amiludin Zahri; Budi Santoso (KINETIKA, 2016)
Oil palm estate in South-Sumatera is very promising for farmers, due to an emp a good prospect as the pulp material standard So that it is necessary to devlop the usage of, that physic waste, by producing the machine that can be used by cluster and stem waste. From the result of production those machines, it is considered to give the contribution to South-Sumatera Provines, not only to cnhanes the income to the region which have the oil palm estate, but also to open new job field in that region. Several prototype machene which can be made contains; chipping, pre-heating, refiner, max-resin applied, dry cyclone, mat-forming is the last machine from the pulp making or production proce last machine from the pulp making or production process. Those machinaes, producss. Those machinaes, produce an innovative, new technology in order to paper inde an innovative, new technology in order to paper industry development.